Yes, I do throw like a girl. An analysis of the social reinforcement of hegemonic masculinity in sport. - Gagnon, Alexandra (My University, 2022)
Female athletes have not only been historically excluded from sport but are fighting for equal competition opportunity in sports today. Traits associated with hegemonic masculinity are embraced in the sporting-community, which asserts the notion of male dominance over women. Hegemonic masculinity is learned by athletes through various socialization processes. This paper begins with a personal statement from the author, then analyzes various factors which contribute to a culture of hegemonic masculinity acceptance within the sporting community. This includes stereotypes in sport, language in sport, segregation, social reinforcement, the dramatization of evil, and stigmatization. It concludes by investigating Canadian female participation in sport today, the measures being taken to improve female retention and participation in Canada. This paper was written for the MacEwan University 2022 Sociology Paper of Excellence competition.
Keywords: women athletes; stereotypes (social psychology) in sports; masculinity in sports; sports for women